Nissen Versus Toupet Fundoplication For Gastro-oesophageal Reflux Disease, Short And Long-term Outcomes. A Systematic Review And Meta-analysis. Issue 2 (8th April 2023) - Salman, Mohamed AbdAlla; Salman, Ahmed; Shaaban, Hossam El-Din; Alasmar, Mohamed; Tourky, Mohamed; Elhaj, Mujahid Gasemelseed Fadlallah; Khalid, Sadaf; Gebril, Mahmoud; Alrahawy, Mahmoud; Elsherbiney, Mohammed; Assal, Mohamed Moustafa; Osman, Mohamed Hosny Abdo; et al.
Abstract : Background: Gastroesophageal reflux disease (GERD) remains one of the most commonly encountered gastrointestinal disorders. Proton pump inhibitors still show an inadequate effect on about 10% to 40% of the patients. Laparoscopic antireflux surgery is the surgical alternative for managing GERD in patients who are not responding to proton pump inhibitors. Aim of the Study: This study objected at comparing laparoscopic Nissen fundoplication and laparoscopic Toupet fundoplication (LTF) concerning the short-term and long-term outcomes. Patients and Methods: This is a systematic review and meta-analysis that evaluated the studies comparing between Nissen fundoplication and LTF for the treatment of GERD. Studies were obtained by searching on the EMBASE, the Cochrane Central Register of Controlled Trials, and PubMed central database Results: The LTF group showed significantly longer operation time, less postoperative dysphagia and gas bloating, less pressure on the lower esophageal sphincter, and higher Demeester scores. No statistically significant differences were found between the 2 groups in the perioperative complications, the recurrence of GERD, the reoperation rate, the quality of life, or the reoperation rate. Conclusion: LTF is favored for the surgical treatment of GERD being of lower postoperative dysphagia and gas bloating rates. These benefits were not at the expense of significantly additional perioperative complications or surgery failure.